Small Dopants Make Big Differences: Enhanced Electrocatalytic Performance of MoS2 Monolayer for Oxygen Reduction Reaction (ORR) by N– and P–Doping - Zhang, Huiying; Tian, Yu; Zhao, Jingxiang; Cai, Qinghai; Chen, Zhongfang (Electrochimica acta, 2017)
[Display omitted] The design and development of low-cost and highly efficient electrocatalysts for oxygen reduction reaction (ORR) is crucial to the large-scale commerical application of fuel cells. Herein, by means of comprehensive densty functional theory (DFT) computations, we explored the potential of the heteroatom doping (N and P) to activate the basal plane of molybdenum disulfide (MoS2) monolayer for ORR in acidic medium. Our computations revealed that substituting S in MoS2 monolayer with N or P atom can introduce high spin density into MoS2 basal plane, leading to its improved chemical reactivity for the O2 activation, and the subsequent ORR steps prefer to proceed though a more efficient 4e pathway. Especially, N-doped MoS2 monolayer exhibits outstanding ORR catalytic performance in terms of its small overpotential (0.67V) and low energy barrier (0.25eV), which is comparable (even lower) to those of Pt–based electrocatalysts. In contrast, the catalytic activity of P–doped MoS2 monolayer is considerably poor due to its very strong interaction with O* and OOH* species in the subsequent reactions. Therefore, we expect that N-doped MoS2 monolayer is a quite promising single-atom-catalyst with high efficiency for ORR in fuel cells.